Pengaruh Media Video Terhadap Hasil Belajar Aqidah Akhlak Siswa Kelas X MA Balongrejo Sumobito Jombang.docx - Adibah Adibah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2021)
This study aims to determine the effect of video media on learning outcomes of aqidah akhlak of class X MA Balongrejo Sumobito Jombang students. This type of research is quantitative with experimental methods. This experiment used 30 students as a sample from 34 population of class X science students and class X social studies students in the 2020/2021 school year. Collecting data in this study with tests in the form of giving pretest and posttest. Non-test data collection using a questionnaire, observation and documentation. For data analysis, the researcher used normality test, homogeneity test and hypothesis test (t-test). The results showed that, in the hypothesis test, the determination of tcount was determined by calculating the t-test. From the calculation of the data, the results of the tcount are smaller than ttable, so the null hypothesis (Ho) is accepted, and the alternative hypothesis (Ha) is rejected. So it can be concluded that there is no effect of learning video media on students' learning outcomes of aqidah akhlak of class X MA Balongrejo Sumobito Jombang students.